Logika dan Rasionalitas Dalam Ilmu - Megawati, Silvia (Journal of Innovation in Teaching and Instructional Media, 2025)
The purpose of this journal research is to explain and analyze the branches of the discipline of Philosophy, as well as to describe the results of thinking that are expressed in written form. Everyone must have different opinions and paradigms. This needs to be expressed in writing, to enrich the research results. The concept of logic and rationality in science is very important in everyday life. Logic and rationality are key components in the scientific method process. The method used in this study is the Systematic Literature Review with a database obtained from Google Scholar. The journal articles used are articles from the last 5 years, namely 2019 - 2024, by paying attention to the keyword’s logic, rationality and science. The results of the analysis of the articles that have been carried out contain a total of 16 research articles consisting of education journals, theology journals, Islamic economics journals, philosophy and theology journals. The conclusion of this study is that by understanding the concept of logic and rationality in science, it is hoped that a better understanding of how the role of logic and rationality in science can be applied in everyday life.